Losada Soler, Elena, y Katarzyna Paszkiewicz (eds.) (2015): Tras la pista: narrativa criminal escrita por mujeres. Barcelona: Icaria Editorial. - Rivero Grandoso, Javier (Revista de Filología Románica, 2017)
Losada Soler, Elena, y Katarzyna Paszkiewicz (eds.) (2015): Tras la pista: narrativa criminal escrita por mujeres